Psychometric properties of observational tools for identifying motor difficulties - a systematic review - P. Asunta; H. Viholainen; T. Ahonen; P. Rintala (BMC, 2019)
Abstract Background Early identification of children with motor difficulties, such as developmental coordination disorder (DCD), is essential. At present only a fraction of children with DCD are identified. The purpose of the study was to systematically review the literature from 1994 to 2017 on observational screening tools and to evaluate the validity, reliability and usability of the questionnaires used. Methods The review of the literature was conducted to synthesize the data from five electronic databases for children aged 6-12 years. The following databases were searched: Academic search Elite (EBSCO), ERIC (ProQuest), MEDLINE (Ovid), PsycINFO (ProQuest), and SPORTDiscus with Full Text (EBSCO). The studies meeting our inclusion criteria were analyzed to assess the psychometric properties and feasibility of the measures. Results The literature search retrieved 1907 potentially relevant publications. The final number of studies that met the inclusion criteria of our systematic review was 45. There were 11 questionnaires for parents, teachers and children. None of the questionnaires was valid for population-based screening as the only measurement tool. Conclusions There are many challenges in using initial screening tools to identify children with motor difficulties. Nevertheless, many promising questionnaires are being developed that can provide information on functional skills and limitations across a variety of tasks and settings in the daily lives of children with DCD. The review provides much needed information about the current scales used in many clinical, educational and research settings. Implications for assessing psychometric properties of the developed questionnaires and further research are discussed. Trial registration PROSPERO, CRD42018087532.